Does a consumer training work? a follow-up survey of the PartecipaSalute training programs - Mosconi Paola; Satolli Roberto; Colombo Cinzia; Villani Walter (BMC, 2012)
Abstract Background When properly trained through training programs on epidemiology, clinical research and healthcare policy, members of patients'/consumers' organizations could be helpful for a patient-oriented healthcare system. Since 2006 the not for profit project PartecipaSalute has organized periodic editions of a training program for representatives of citizens'/patients' organizations. After five editions of this training program, a survey of the long-term satisfaction and the impact on activities has been carried out. Methods A 17-questions follow-up questionnaire has been developed. The sample comprised 99 people who had taken part in at least one program edition. Results The overall response rate was 89% (89 responders/99 participants). About 98% of participants expressed general satisfaction with the training program and with the knowledge gained. Medical and informative topics were rated better than technical ones for their usefulness (96% versus 86%). The results of the survey showed a strong impact of the training course on single participants, while a weak outcome on the activities of the organizations was reported. Conclusions The training program was positively rated, and improvements in personal knowledge were reported. Less impact was reported on organizations' activities. Participants showed a remarkable willingness to get more involved in healthcare decisions, and to boost their knowledge of health and research issues. The results show the importance of follow-up to understand the real value of training program and to better organize future programs.